KORELASI PENGALAMAN PRAKTIK KERJA INDUSTRI DENGAN KESIAPAN SISWA MENGHADAPI DUNIA KERJA - Edriati, Sofia; Pratama, Ade; Masril, Maini Hikmawati (STKIP PGRI Sumatera Barat, 2020)
Industrial work practices can form constructive mindsets for students, especially in preparing themselves for the world of work. This study aims to determine the correlation between experiences of industrial work practices with the readiness of students in dealing with the world of work. This research is a correlation study. This research was conducted at the SMKN 6 Padang with 30 students as a subject of class XII TKJ. The instrument used was a questionnaire of work practices experiences and work readiness questionnaire. The data analysis technique used is simple linear regression analysis. The results of data analysis show that there is a positive correlation between the experiences of industrial work practices with the work readiness of students.